Pengembangan Budaya Literasi di Perguruan Tinggi Keagamaan Islam Melalui Peer Tut - Gustini., Neng; Imani, Anugrah; Rohaniawati., Dede (Kebudayaan, 2018)
AbstractThis study based on phenomenon about literacy culture of Indonesian community is low. The problems of this research are: (1) Why tradition of literacy in Tarbiyah and Teaching Faculty of Sunan Gunung Djati Islamic University is weak?; (2) How to improve tradition of literacy in Tarbiyah and Teaching Faculty?; (3) Why is it necessary to improve the literacy tradition of Peer Tutors?This study focuses on three purposes: (1) Identify literacy culture program on students in Tarbiyah and Teaching Faculty of Sunan Gunung Djati Islamic University before using peer tutor; (2) Describe implementation process of multiple intelligences through peer tutor on students’ literacy culture: (3) Explain the results of development of students’ literacy culture based on multiple intelligences through peer tutor. The method of this research is research and development. The result shows that literacy programs in Tarbiyah and Teaching Faculty of Sunan Gunung Djati Islamic University before using peer tutor have not been planned systematically, only structured learning, such as: papers, book reports and observation reports. Whereas literate culture by using multiple intelligences through peer tutor program can improve the culture of reading and writing because it was implemented using the programs as follows: Drop Everything and Read (DEAR) program: One Day One Article (ODOA) program, and One Month One Book (OMOB) program. Those activities were carried out by literacy community (KOMBIS). Besides, there was the implementation of literacy Journal, workshop, and has created literacy community which consist of 15 students who have the same programs on multiple intelligences.Abstrak :Penelitian ini bertitik tolak dari fenomena rendahnya budaya literasi masyarakat Indonesia. Permasalahannya adalah: (1) Mengapa tradisi literasi di Fakultas Tarbiyah dan Keguruan (FTK) UIN Sunan Gunung Djati lemah? (2) Bagaimana meningkatkan tradisi literasi di FTK UIN Sunan Gunung Djati? (3) Mengapa untuk meningkatkan tradisi literasi perlu Peer Tutor? Fokus penelitian adalah: (1) mengidentifikasi program budaya literasi mahasiswa di FTK UIN Sunan Gunung Djati sebelum menggunakan tutor sebaya, (2) mendeskripsikan proses implementasi kecerdasan majemuk melalui tutor sebaya pada budaya literasi mahasiswa, (3) menjelaskan hasil pengembangan budaya literasi berbasis kecerdasan majemuk melalui tutor sebaya. Metodologi yang digunakan adalah penelitian pengembangan (R&D). Hasilnya menunjukkan bahwa program literasi di FTK UIN Sunan Gunung Djati Bandung sebelum menggunakan tutor sebaya belum terencana secara sistematis, pembelajaran hanya dilakukan secara terstruktur seperti: makalah, laporan buku dan laporan observasi. Realitas budaya literasi dengan menggunakan kecerdasan majemuk melalui peer tutor dapat meningkatkan budaya membaca dan menulis karena diimplementasikan dengan menggunakan: Drop Everything and Read (DEAR) program; One Day One Article (ODOA) program, dan One Day One Book (ODOB) program. Kegiatan tersebut dilakukan oleh komunitas literasi (KOMBIS) di UIN. Selain itu, penelitian ini menghasilkan jurnal literasi, workshop, dan telah menciptakan komunitas literasi yang terdiri dari 15 mahasiswa.